2020
DOI: 10.1002/jbm.a.36943
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of stromal cell–derived factor‐1 alpha from silk fibroin microfiber promotes urethral reconstruction in rabbits

Abstract: We developed a stromal cell–derived factor‐1 alpha (SDF‐1α)‐aligned silk fibroin (SF)/three‐dimensional porous bladder acellular matrix graft (3D‐BAMG) composite scaffold for long‐section ventral urethral regeneration and repair in vivo. SDF‐1α‐aligned SF microfiber/3D‐BAMG, aligned SF microfiber/3D‐BAMG, and nonaligned SF microfiber/3D‐BAMG scaffolds were prepared using electrostatic spinning and wet processing. Adipose‐derived stem cell (ADSC) and bone marrow stromal cell (BMSC) migration was assessed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…These scaffolds are loaded with biochemical and biophysical clues to recruit endogenous cells for tissue healing. As alternatives to autografts, artificial urethra made of natural degradable biomaterials (such as collagen and SF) are promising candidates in terms of tissue integration, 5,15–17 but lack the capability to induce tissue regeneration due to the bio‐inert characteristics. Hence, the manufacture process of bioactive or bio‐functional urethral grafts has been widely explored through the application of surface modifications and the addition of bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These scaffolds are loaded with biochemical and biophysical clues to recruit endogenous cells for tissue healing. As alternatives to autografts, artificial urethra made of natural degradable biomaterials (such as collagen and SF) are promising candidates in terms of tissue integration, 5,15–17 but lack the capability to induce tissue regeneration due to the bio‐inert characteristics. Hence, the manufacture process of bioactive or bio‐functional urethral grafts has been widely explored through the application of surface modifications and the addition of bioactive molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In situ tissue‐engineering using degradable biomaterials can utilize the regeneration potential of human body through reasonable scaffold design (including structural optimization and functionalization) and reproduce natural tissue regeneration 14 . In this field, some studies have shown that in situ tissue‐engineered scaffolds produced new urethras nearly free of foreign materials in vivo 15–17 . However, few of them can reproduce the biological function of damaged urethra in the early stage of transplantation, and there are difficulties in subsequent lumen epithelial tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations